Impure Mouths and Defiled Hearts: The Development of Deceit Impurity in Second Temple Judaism - Moshe Blidstein (Religions, 2022)
Many early Christian and late Second Temple texts describe deceit as impurity. In this article, I delineate the development of this discourse and argue that it derived its power from several characteristics: mixing deceit impurity with other types of moral impurity; an implicit link between the structures of defilement/purity and falsehood/truth; localization of impurity in specific body loci; demonization; and a connection with Greek discourses on sophists and magicians. Some of these features are present already in the earliest texts such as the Hebrew Bible, but others developed only in the Hellenistic period.